Sosialiasi Pendidikan dan Literasi Hukum untuk Gen-Z dan Alpha - Miharja, Marjan; Budi, Arrum; Windyastuti, Feny; Yuwafi, Rani; Fakhlur , Fakhlur; Fitryantica, Agnes; Sutrisno, Andri; Kemala, Ratih; Hamka, Vinoti; Prasetiyo, Wahyu (CV. Era Digital Nusantara, 2025)
Real Work Lecture (KKN) is a form of implementation of Independent Learning Independent Campus which is a policy of the Minister of Education and Culture, which aims to encourage students to master various sciences that are useful to enter the world of work. The Merdeka Campus provides an opportunity for students to choose the courses they will take. This Independent Learning-Independent Campus Policy is in accordance with PERMENDIKBUD Number 3 of 2020 concerning National Standards for Higher Education. KKN is a form of community service carried out by students in an interdisciplinary, institutional, and partnership manner as a form of Catur Dharma in higher education. KKN is a form of lecture that is carried out through community empowerment programs. The communities targeted by KKN can be rural communities, urban communities, schools, industrial communities, or other community groups that are considered worthy of being targeted by KKN. The approach method used is counseling with powerpoint media with the theme of literacy. The literacy presented was about the laws that exist in society such as the importance of counteracting ITE crimes, hate speech, hoaxes and SARA as well as literacy about the impact of bullying, norms, manners, and ethics in society, especially on parents, bullying, norms, manners, ethics, and the wise use of social media with children and adolescents at SMA Muhammadiyah 4 Jakarta.